2020
DOI: 10.1002/fsn3.1718
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bio‐accessibility, polyphenol profile and antioxidants of quinoa and djulis sprouts during in vitro simulated gastrointestinal digestion

Abstract: This study aimed to evaluate the bio‐accessibility of the phenolics and flavonoid, the polyphenolic profile and the antioxidant activity of sprouts obtained from four different quinoa genotypes and one djulis cultivar during in vitro gastrointestinal digestion. Compared to their content in sprouts, the bioavailable phenolics after the oral phase, the gastric phase, the intestinal phase, and in the dialyzable fraction were in the ranges of 45.7%–63.5%, 87.6%–116.7%, 89.6%–124.5%, and 7.4%–10.9%, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
(56 reference statements)
5
13
0
Order By: Relevance
“…Quinoa leaves and seeds contain different types of phenolic acids and their derivatives hydroxycinnamic acid and hydroxybenzoic acid, which possess considerable health-promoting activities such as antihypertensive, anti-oxidative, antidiabetic, anti-inflammatory and anticarcinogenic effects. The concentration of phenolic acids in quinoa seeds varies from one to other variety [98][99][100][101][102][103][104] (Table 3 and Figure 2). Four varieties of white (Q-w1), red (Q-r1 and Q-r2) and black (Q-b1) and three varieties of white (Q-w2), red (Q-r3) and black (Q-b2)…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoa leaves and seeds contain different types of phenolic acids and their derivatives hydroxycinnamic acid and hydroxybenzoic acid, which possess considerable health-promoting activities such as antihypertensive, anti-oxidative, antidiabetic, anti-inflammatory and anticarcinogenic effects. The concentration of phenolic acids in quinoa seeds varies from one to other variety [98][99][100][101][102][103][104] (Table 3 and Figure 2). Four varieties of white (Q-w1), red (Q-r1 and Q-r2) and black (Q-b1) and three varieties of white (Q-w2), red (Q-r3) and black (Q-b2)…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…[101] Quercetin 3-O-(2,6-di-α-Lrhamnopyranosyl)-β-Dgalactopyranoside [85] Quercetin 3-O-(2,6-di-α-Lrhamnopyranosyl)-β-Dgalactopyranoside [85] Quercetin-3-O-(2 -apiosyl)-rutinoside [85] Quercetin glucuronide [101,102] Kaempferol…”
Section: References Flavonoidsmentioning
confidence: 99%
“…Previous studies showed that HTS and OLE concentrations remain stable during OPE digestion, while the amount of bioaccessible TS increases significantly in comparison to native, undigested sample [11]. Other authors have also shown that polyphenolic composition of food-or plant-derived extracts and consequently their biological activity is significantly affected by gastrointestinal digestion [12][13][14]. The presence of CDs in the formulation also affected the bioaccessibility of polyphenolic antioxidants by increasing bioaccessibility of TS, probably by formation of inclusion complexes and prevention of TS adhesion to bile salts or other macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the phenolic compounds present in plants are formed during their development and under stress conditions; these include simple phenols, phenolic acids, coumarins, flavonoids, stilbenes, hydrolysable and condensed tannins, lignans, and lignins [19]. Additionally, these polyphenols could be altered during the germination process, increasing their content and the antioxidant capacity [20].…”
Section: Discussionmentioning
confidence: 99%